Cover Picture: Photoinduced Charge‐Carrier Generation in Epitaxial MOF Thin Films: High Efficiency as a Result of an Indirect Electronic Band Gap? (Angew. Chem. Int. Ed. 25/2015). Issue 25 (27th May 2015) - Liu, Jinxuan; Zhou, Wencai; Liu, Jianxi; Howard, Ian; Kilibarda, Goran; Schlabach, Sabine; Coupry, Damien; Addicoat, Matthew; Yoneda, Satoru; Tsutsui, Yusuke; Sakurai, Tsuneaki; Seki, Shu; et al.
<x xml:space="preserve">Abstract</x> Strictly periodic assemblies …︁ …︁ of porphyrin units deposited on functionalized substrates can be used to realize solar cells with remarkable efficiency. In their Communication on page 7441 ff., J. Liu, C. Wöll, and co‐workers show by electronic‐structure calculations that ordered arrays of porphyrins have a small dispersion of occupied and unoccupied bands leading to the formation of a small indirect band gap. Such ordered porphyrin metal–organic frameworks (MOFs) are then grown using a layer‐by‐layer liquid‐phase epitaxy.